Climate Change: The Biggest Challenge in 21st Century - Iqbal, Badar Alam; Ghauri, Farha Naaz (Richtmann Publishing, 2011)
Climate change is the biggest challenge for the mankind in the present century. The world is speeding towards aclimate catastrophe. Our foot is stuck on the accelerator and we are heading towards an abyss. It has far reaching effects,consequences and implication for entire globe in general and developing countries in particular. If sincere efforts are not madeon war footing, then the life would become hell on this planet. These days, seasons are changing, temperature is rising of bothearth and seawater and there is no end to it. The globe is entering in era wherein the environment would get intertwined in aspiral of decline and degradation affecting the availability and access to water, food, and energy in a big way. According to astudy, world over people would consume 10 per cent more water per year than nature could replenish. Increase in globalwarming has been melting glaciers and receding snowlines. Accordingly, seventy rivers have stopped flowing into the sea andas a result, aquifers are depleting. Our foot is stuck on the accelerator and we are heading towards an abyss. It has far reachingeffects, consequences and implication for entire globe in general and developing countries in particular. If sincere efforts are notmade on war footing, then the life would become hell on this planet. These days, seasons are changing, temperature is rising ofboth earth and seawater and there is no end to it. Hence, it is high time that globe as a whole must come forward to formulate acollective strategy for meeting or facing the biggest challenge of 21st century. Both developed and developing nations are sailingin the same boat. Both must take lesson from Japanese disaster. Hence, it is high time that globe as a whole must come forwardto formulate a collective strategy for meeting or facing the biggest challenge of 21st century.